Anthropometric study on children of Garo and non-Garo families in Netrakona district of Bangladesh (Journal of the Bangladesh Agricultural University, 2012)
Anthropometric indicators such as weight-for-height (wasting), height-for-age (stunting) and weight-for-age   (underweight) are important in evaluating the health and nutrition status of children in low-income areas of   Bangladesh where malnutrition is still a large public health problem. Present investigation was carried out to assess   the anthropometric status of tribal (Garo) and non tribal women of different villages of four Unions of Kalmakanada   upazila under Netrakona district. Data were collected through well structured questionnaire. Total one hundred   seventy families, ninety from tribal (Garo) and one hundred eighty from non-tribal constituted the sample of the study.   The results show that malnutrition problem in this area is common due to poverty and children have low weight, under   height, wasting and malnourished. The hierarchical interrelationships of potential determinants of malnutrition,   wasting and underweight turned out to be independently predicted by morbidity factors. Stunting, however, was   predicted by socioeconomic, environmental and health-care factors in addition to morbidity. Strategies aimed at   improving the growth of infants and young children in rural communities should address morbidity due to common   childhood illness coupled with environmental and socio-economically oriented measures.   DOI: http://dx.doi.org/10.3329/jbau.v9i2.11039   J. Bangladesh Agril. Univ. 9(2): 267272, 2011